Fear voting: Securitization of migration in the context of European parliament election 2019 in the Czech Republic - Brozik, Martin (AUC Knowledge Fountain, 2020)
This thesis is devoted to the phenomenon of securitization of migration. This phenomenon is observed on a case study of Election campaigns before the EU Parliament election in May 2019 in the Czech Republic. The thesis looks into if and how the relevant political parties used securitization of migration in their election manifestos. By using a combination of a disciplined interpretive case study and content analysis, a framework is created based on Thierry Balzacq's theory on securitization. The content analysis uses the scope of various levels (context, attributes, statements) to identify individual securitization speech acts. This thesis sees securitization on as a one-way process but instead incorporates the process of communication between the political party and the electorate. The results show that majority of the researched parties used securitization of migration in their manifestos and created a notion of a direct threat to security caused by either those migrants who already got into Europe or those who are deemed to come according to some of the political parties. It also shows that more prone to accepting securitization of migration are older voters with lower levels of education who are in general dissatisfied with the development of their living situation after the 1989 revolution. Further significant factors are described using the theories of various researchers, e.g. deep-history theory, a theory of peripherality and feeling of being left out. These theories offer possible additional explanations on voters' preferences and the vulnerability towards accepting the securitization of migration. Even though this thesis focuses only on the case of the Czech Republic, it can be expected that the results can be generalized and to some extent applied to other countries in the region, mainly on the other members of the Visegrad group, given their shared history as well as similar challenges faced by today's political representations in these countries.